2018
DOI: 10.1017/s0950268818002443
|View full text |Cite
|
Sign up to set email alerts
|

Implementing large Foot and Mouth Disease vaccination programmes for smallholder farmers: lessons from Lao PDR

Abstract: This study assessed smallholder finances and their attitudes towards the Foot and Mouth Disease (FMD) vaccination programme, when 1 620 000 vaccine doses were provided for strategic administration in large ruminants in FMD 'high-risk' areas in Laos between 2012 and 2016. Farmers (n = 168) in the provinces of Xayyabouli (XYL), Xiengkhoung (XK) and Huaphan (HP), were interviewed. Over 91% of the farmers responded that their livestock were vaccinated for FMD, with over 86% ranking FMD vaccination as a good or ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…The lower rate of households impacted with FMD than expected was considered attributable to FMD vaccination that had been conducted in the village 5 months previously using a commercially available bivalent O and A vaccine (Boehringer Ingelheim, France) that was residual from a previous vaccination campaign, as previously described. 8 Of the village's large-ruminant population, 52 buffalo and nine cows had been vaccinated for FMD (Table 1). Although present in the village, no goats or pigs had been vaccinated for FMD, and none was observed or reported to have been affected by FMD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower rate of households impacted with FMD than expected was considered attributable to FMD vaccination that had been conducted in the village 5 months previously using a commercially available bivalent O and A vaccine (Boehringer Ingelheim, France) that was residual from a previous vaccination campaign, as previously described. 8 Of the village's large-ruminant population, 52 buffalo and nine cows had been vaccinated for FMD (Table 1). Although present in the village, no goats or pigs had been vaccinated for FMD, and none was observed or reported to have been affected by FMD.…”
Section: Resultsmentioning
confidence: 99%
“…19 Numerous investigations of FMD outbreaks in Laos have demonstrated that clinical FMD has largely been confined to large ruminants. 1,[7][8][9][10][11] Recent serological investigations have confirmed that there has been occasional transmission of FMDVs in goats in Laos, although this has not been recorded in Luang Prabang, where this outbreak occurred. 22 This novel approach to FMD-outbreak management may also provide disease-control benefits from the likelihood of viricidal activity of this product against FMDVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In partnership with SEACFMD, the Australian government funded the Stop Transboundary Animal Diseases and Zoonoses (STANDZ; 2011–2016) initiative providing important technical and financial contributions toward control of FMD in South East Asia ( 6 ). Routine FMD vaccination was a key component of the STANDZ initiative and involved the administration of 1.6 million doses of bivalent (serotype O and A) or monovalent (O) FMD vaccines to large ruminants in northern Laos between 2012 and 2016 ( 7 ). Due to the vaccine sourcing strategy conducted by the OIE vaccine banks, the vaccines are guaranteed to be high quality but may be produced by numerous different reputable manufacturers ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…With market demands in China and Vietnam, there is increased migration of goats, along with large ruminants, through Laos in to these markets ( 10 ). Goats are rarely vaccinated for FMD in South East Asia, cattle, and buffalo are often vaccinated when donor supported official FMD vaccination programs occur in Laos ( 7 ). However, goats are occasionally vaccinated but only during an outbreak response.…”
Section: Introductionmentioning
confidence: 99%